A new species of Pisionidens (Aiyar & Alikunhi, 1943) (Annelida: Sigalionidae) from Southeastern Brazil - Miranda, Vinícius Da Rocha; Brasil, Ana Claudia Dos Santos; Santos, Cinthya Simone Gomes (Zootaxa, 2016)
Herein we describe specimens found along the southeastern coast of Brazil which belong to a new species, P. caissara sp. nov. This species differs from the other species of the genus by the glabrous antennae and palps, proboscis extending up to the sixth segment, jaws with smooth cutting edge and a pair of lateral wing-like sheaths, two pairs of seriate male copulatory organs, first pair of testes on segment 19 and ovaries from segment 26 onward. Reproductive characters commonly used for characterizing species are also discussed.